2012
DOI: 10.1007/s11033-012-2261-0
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin- and ubiquitin-like proteins-conjugating enzymes (E2s) in breast cancer

Abstract: Breast cancer is the most common malignancy in women and a significant cause of morbidity and mortality. Sub-types of breast cancer defined by the expression of steroid hormones and Her2/Neu oncogene have distinct prognosis and undergo different therapies. Besides differing in their phenotype, sub-types of breast cancer display various molecular lesions that participate in their pathogenesis. BRCA1 is one of the common hereditary cancer predisposition genes and encodes for an ubiquitin ligase. Ubiquitin ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 131 publications
0
22
0
Order By: Relevance
“…Ubiquitination is a significant post-translational modification process in which the modified proteins are attached to the Ub, and their stability and functions in multiple cell processes and diseases, especially cancer development, are regulated 19 , 20 . Wu and Zhang 21 found that the phosphorylation of EZH2 at the Thr-345 and Thr-487 sites promoted the ubiquitination of EZH2 and subsequent degradation by the ubiquitin–proteasome pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination is a significant post-translational modification process in which the modified proteins are attached to the Ub, and their stability and functions in multiple cell processes and diseases, especially cancer development, are regulated 19 , 20 . Wu and Zhang 21 found that the phosphorylation of EZH2 at the Thr-345 and Thr-487 sites promoted the ubiquitination of EZH2 and subsequent degradation by the ubiquitin–proteasome pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The E2 enzyme UBE2B, increases the polyubiquitination of β-Catenin, a protein that is frequently upregulated in cancer cells [ 24 ]. In addition, UBE2B cooperates with MDM2, an E3 Ub ligase, in a complex to assist the ubiquitination and degradation of the p53 tumor suppressor [ 25 ].…”
Section: Ubiquitination and Sumoylation In Prostate Cancermentioning
confidence: 99%
“…This catalytic core domain is known as the Ub iquitin C onjugation (UBC) domain and contains the catalytic cysteine, which forms a thioester bond with Ub 45 46 47 . E2s recently gained attention as targets to design inhibitory molecules 49 50 51 52 53 since their aberrant regulation is associated with cancer or neurodegenerative diseases 54 55 56 .…”
mentioning
confidence: 99%